Face of Poverty in Madagascar : Poverty, Gender, and Inequality Assessment - World Bank (Washington, DC, 2014)
Madagascar has been entirely unsuccessful in reducing the number of its people that are poor, or extremely so, in the ten years since 2001, when poverty was already at a very high level. This well-known conclusion draws on the analysis of three successive rounds of the national household expenditure surveys (enquete periodiques aupres des menages, EPM) conducted by the Madagascar National Institute of Statistics (INSTAT) in 2001, 2005, and 2010. The objective of the analysis in this report is to document the levels and changes in poverty in Madagascar, and provide a detailed review of correlates of poverty and inequality in various dimensions, including gender, age, the structure of households, and place of residence. The report is an assessment of past poverty trends, and while policy implications are highlighted in many cases, the report is focused mainly on the descriptive, rather than prescriptive. It is found that the poverty headcount did not decrease between 2001 and 2005, rising instead from 71 to 75 percent of the population, rather than the 68 percent estimated official headcount for 2005. The methodology is described at length in the report and its annexes.